A Critical Analysis of E-Governance Reforms and Its Implications on Education and Police Department: A Case Study of Mardan (British Journal of Multidisciplinary and Advanced Studies, 2023)
This paper explores to investigate the role of E- governance reforms and its implications on education and police department. E- governance stands for electronic governance; it is a unification of information and communication technology(ICT) all the operation used for to augment the potential of the government to satisfy the requirements of the public and ensure accountability and adoptability at all the levels. The E- governance denotes not only to increase the productivity of the governance but also inevitable to curb corruption, promote transparency and also provide a viable pathway for citizens to directly participates in their government. E- governance is a global phenomenon, has played a very crucial role in the contemporary world politics and led to increase the effiiciency of the government services. This research paper sheds light on the nature and reforms of E- governance and its attributes linkage with the practical implemented reforms in the two distinct department; Education and police and it also discusses how it is necessary for good governance and sustainable development.  This article argues that E-governance is more yielding in the way of good governance. The investigation discovered with the help of major findings due to comparative study of two departments that E-governance strengthen and guide good governance, provides a conducive environment for the safeguarding of human rights, sustainable ecomomic growth, efficient services delivery and incentivise citizens to increase their participation and develop a mechanism for measuring and showcasing the level of citizen participation. . Research focused on major contribution and implementation of E- governance in district Mardan, particularly in the education and police department.